Ballistic Performance and Microstructure of Tempered AISI 4130 Steel - Ilham Aminudin; Sovian Aritonang (ELEMEN : JURNAL TEKNIK MESIN, 2022)
Heat treatment methods are generally carried out to increase ductility, increase hardness, increase metal tensile stress, and so on. AISI 4130 steel is commonly used for manufacturing equipment, vehicle parts, stone-crushing machines to body armor. To improve the quality of the steel, heat treatment is required by providing austenitizing and tempering processes. This study aims to determine the hardness, density, and ballistic performance of AISI 4130 steel after tempering at 290oC. The results of experiments on AISI 4130 steel which has been tempered at a temperature of 290oC with a time of 90 minutes. Gets a hardness of 45 HRC. For the density test, the result is 7.85 g/cm3. With the results of the ballistic test getting the numbers V = 635 m/s and V50 = 600 m/s, the penetration mode is plugging.